Kilabot at kembot (Viva Video., 2002)
The murder of his long-time partner 'Kamandag'- He tried to obtain justice for his comrade but failed because the culprit was able to escape. Leon after sometime, decided to retire from being a secret agent and concentrate on his career as a tattoo artist. One day, he meets a gorgeous lady named Sienna, a college coed and immediately falls in love with her. Little did he know that Sienna is a stripteaser and she is actually the personal private dancer of Chino Guevarra, the head of a big time syndicate responsible for the series of kidnappings in the city who happens to be same person responsible for 'Kamandag' murder.